Respiratory syncytial virus–associated illness in adults with advanced chronic obstructive pulmonary disease and/or congestive heart failure - Falsey, Ann R; Walsh, Edward E; Esser, Mark T; Shoemaker, Kathryn; Yu, Li; Griffin, M Pam (Journal of medical virology, 2019)
Background Respiratory syncytial virus (RSV) is recognized as a serious pathogen in people with chronic cardiopulmonary conditions. Immunoprophylaxis might be considered for adults at high‐risk for frequent and severe RSV infection. Thus, we studied the incidence of RSV‐related medically attended acute respiratory illness (MARI) in adults with severe chronic obstructive pulmonary disease (COPD) and/or congestive heart failure (CHF). Methods Subjects ≥50 years of age with Gold Class III/IV COPD and/or American Heart Association class III/IV CHF and exposure to children ≥once per month were recruited. Subjects were evaluated over 1.5 to 2.5 years for RSV‐associated MARI, defined as polymerase chain reaction (PCR) and/or seroresponse. Results Four hundred forty‐five subjects were enrolled between October 2011 and May 2012. Overall, 99 RSV infections were documented by PCR or serology for a cumulative incidence of 22.2%. Of these, 42 (9.4%) subjects had protocol‐specified RSV‐MARI for an incidence of 4.68/100 patient‐seasons. All‐cause MARI was common (63.85/100 patient‐seasons) with rhinovirus most commonly identified. Conclusion RSV infection was common in adults with severe COPD and/or advanced CHF. Given the severity of underlying cardiopulmonary diseases in the study population, most illnesses were surprisingly mild. Thus, active immunization rather than passive immunoprophylaxis with monoclonal antibodies may be a more cost‐effective strategy.